The Possibility of Vice-Presidentsâ€™ Authority Arrangement in the 1945 Constitution through Constitutional Amendment - Suroso, Fajar L. (Hasanuddin Law Review, 2016)
The debate over the vice-presidentsâ€™ authority reappeared in the administration of President Jokowi after the â€œauthority expansion of the Chief of Presidency Staffâ€ and the case of â€œRizal Ramli vs Jusuf Kallaâ€. This article is intended to provide arguments for the idea of some parties to organize more explicit and detailed the authority of vice-president in the 1945 Constitution. The idea arises from the absence of further arrangement on the authority of vice-president in the 1945 Constitution. This article is systematized into 3 (three) sub-theme; 1) the arrangement of the vice-presidentsâ€™ authority in the constitution for several countries; 2) The authority of the vice president according to the 1945 Constitution, and 3) New resultant and the possibility of 1945 Constitution amendment. The result revealed a number of interesting things; 1) the constitutions of other countries do not specify the authority of the vice-president and put the vice-president as a â€œspare tireâ€ when the president is absent; 2) no new resultant about the position and authority of the vice-president so that theoretically is not reason enough to regulate in detail the authority of the vice-president through the 1945 Constitution amendment; 3) arrangement in detail in the authority of vice-president in the 1945 Constitution holds the potential to confuse the presidential system design as the 1945 Constitution. Therefore, the possibility of vice-presidentsâ€™ authority arrangement in the 1945 Constitution through amendment is very small, both in terms of momentum and the substance of issues.